ANALISIS SEMIOTIK FILM ALANGKAH LUCUNYA NEGERI INI - Riki Chandra; Ilham Firdaus; Ernita Arif; Elva Ronaning Roem (IAI Darussalam, 2021)
This study describes and analyzes the function of film in conveying an idea or message in audio-visual form. Films are a medium of entertainment but also contain educational values ??(education), social control, and so on. Films as a means of conveying information in mass communication are also capable of presenting messages broadly in a short time, as is characteristic of other mass media. This study uses a semiotic analysis study. Semiotic analysis method is the study of signs or those associated with them, how they function, their relationship with other signs, their delivery and acceptance by those who use them. This study uses a qualitative method. The data collection process was carried out by observation. The results showed that the overall message that dominates this film is a message about education that occurs in Indonesia. The moral message contained in this film concerns the rights of neglected children, street children who do not get formal education. Contrary to the 1945 Constitution, Article 31, the first paragraph which states that every citizen has the right to education, and in the second paragraph every citizen is obliged to attend basic education and the government is obliged to pay for it.